1995
DOI: 10.1016/s0092-8674(05)80014-5
|View full text |Cite
|
Sign up to set email alerts
|

Mouse egg integrin α6β1functions as a sperm receptor

Abstract: Binding between sperm and egg plasma membranes is an essential step in fertilization. Whereas fertilin, a mammalian sperm surface protein, is involved in this crucial interaction, sperm receptors on the egg plasma membrane have not been identified. Because fertilin contains a predicted integrin ligand domain, we investigated the expression and function of integrin subunits in unfertilized mouse eggs. Polymerase chain reactions detected mRNAs for alpha 5, alpha 6, alpha v, beta 1, beta 3, and beta 5. Immunofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
358
4
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(376 citation statements)
references
References 54 publications
11
358
4
3
Order By: Relevance
“…Several integrin subunits are expressed on human and/or murine preimplantation embryos [7], [8]. Their function in embryonic development is not fully understood, but some, such as the α5 chain, are clearly individually important after implantation [26], [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several integrin subunits are expressed on human and/or murine preimplantation embryos [7], [8]. Their function in embryonic development is not fully understood, but some, such as the α5 chain, are clearly individually important after implantation [26], [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although cadherins are thought to be primarily responsible for the cell-cell adhesion seen in early vertebrate embryos [4], [6], a variety of integrin subunits have been detected on mouse and human preand peri-implantation embryos, including 1, 3, 5, 6, 7, V, 1, 3, 4, 5 [7][8][9]], suggesting that these molecules may play a role in embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…Global deletion of Itgb1 in mice results in lethality during early post-implantation [35,36]. We thus exam- ined the effect of partial and complete elimination of Itgb1 in dorsal telencephalic progenitors by crossing the Itgb1 f/f or Itgb1 f/+ mice [37] with the Emx1-Cre transgenic mice [38], respectively.…”
Section: Itgb1 Is Required For Axon Formation In Cortical Neurons In mentioning
confidence: 99%
“…A proteolytic processing mechanism removes the pro-and metalloprotease domains, displaying the disintegrin domain at the N-terminus of the fertilin ␣ and ␤ Lum and Blobel, 1997). Peptides containing the disintegrin domain are known to bind to ␣II␤3 integrin present in platelets (Adler et al, 1991) and fertilin ␤ has been shown to bind to ␣6␤1 integrin present on the egg plasma membrane (Almeida et al, 1995). ␣3␤1 and ␣6␤1 integrins are expressed by both testicular somatic and spermatogenic cells (Schaller et al, 1993;Salanova et al, 1995) during fetal and postnatal testicular development (Frojdman and Pelliniemi, 1994) and in Sertoli-PSG cocultures (Rosselot et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to fertilin ␣ and fertilin ␤, the gene expression of several members of the ADAM family has been detected in somatic and spermatogenic cell components of prepubertal and adult rat testis and other organs (Frayne et al, 1997). An ␣6␤1 integrin receptor on mouse egg plasma membrane acts as the sperm receptor to which the disintegrin domain of fertilin ␤ binds (Almeida et al, 1995). It has been reported that fertilin ␤ but not fertilin ␣ displays adhesive activity by interacting with ␤1 integrin (Evans et al, 1997).…”
Section: Introductionmentioning
confidence: 99%